2016
DOI: 10.1002/ijop.12262
|View full text |Cite
|
Sign up to set email alerts
|

PATHS in Croatia: A school‐based randomised‐controlled trial of a social and emotional learning curriculum

Abstract: This study represents the first rigorous evaluation of a social-emotional learning curriculum, PATHS (Promoting Alternative Thinking Strategies; Kusché & Greenberg, 1994), in elementary schools in Croatia. This study randomly assigned 29 schools to receive the universal preventive intervention or continue with usual practices. Within those schools, this study included 57 classrooms and 568 children. Teachers rated nine child behaviours in the middle of first grade (pre-intervention) and near the end of second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Research shows that implementation of evidence-based SEL interventions and programs can improve both immediate and long-term social-emotional competencies, resulting in direct and measurable academic gains and helping make a meaningful difference in schools and in children's lives Taylor et al, 2017). Studies broadly reflect the meta-analyses findings that SEL programs are accomplishing social-emotional outcomes, improving behavior and increasing academic achievement, most notably at early childhood and elementary level (Bierman et al, 2010;Flook et al, 2015;Haslip et al, 2018;Jones et al, 2011;Martínez, 2016;Novak et al, 2017;Raimundo et al, 2013;Schonert-Reichl et al, 2015;Schonfeld et al, 2015;Zhai et al, 2015). However, challenges and limitations have been found that impede the effectiveness of SEL programs, with findings continuing to be mixed in the literature (Coelho and Sousa, 2018;Zhai et al, 2015).…”
Section: Research On Social and Emotional Learningmentioning
confidence: 99%
“…Research shows that implementation of evidence-based SEL interventions and programs can improve both immediate and long-term social-emotional competencies, resulting in direct and measurable academic gains and helping make a meaningful difference in schools and in children's lives Taylor et al, 2017). Studies broadly reflect the meta-analyses findings that SEL programs are accomplishing social-emotional outcomes, improving behavior and increasing academic achievement, most notably at early childhood and elementary level (Bierman et al, 2010;Flook et al, 2015;Haslip et al, 2018;Jones et al, 2011;Martínez, 2016;Novak et al, 2017;Raimundo et al, 2013;Schonert-Reichl et al, 2015;Schonfeld et al, 2015;Zhai et al, 2015). However, challenges and limitations have been found that impede the effectiveness of SEL programs, with findings continuing to be mixed in the literature (Coelho and Sousa, 2018;Zhai et al, 2015).…”
Section: Research On Social and Emotional Learningmentioning
confidence: 99%
“…The aim of this part of the chapter is to present two studies of empirical evaluation of socialemotional learning curriculum, Promoting Alternative Thinking Strategies (PATHS) [66], conducted in Croatian kindergartens [67] and elementary schools [68] in order to examine the effects on the level of internalized problems such as emotional withdrawal, depressive symptoms, and worry.…”
Section: Research Studiesmentioning
confidence: 99%
“…In this issue, Novak, Mihic, Basic, and Nix () report data from a randomised controlled effectiveness trial of an evidence‐based universal prevention programme, PATHS (Promoting Alternative Thinking Strategies; Kusché & Greenberg, ), adapted for elementary schools in Croatia. This study represents the first rigorous evaluation of a social‐emotional learning programme for youth in Croatian schools, using intent‐to‐treat analysis to examine effects of the programme on 568 children in 57 classrooms and 29 schools in three cities.…”
Section: Evaluating Interventions With Rctsmentioning
confidence: 99%